2023
DOI: 10.3390/min13081004
|View full text |Cite
|
Sign up to set email alerts
|

Petrographic Evaluation of Aggregate from Igneous Rocks: Alkali–Silica Reaction Potential

Aneta Antolik,
Mariusz Dąbrowski,
Daria Jóźwiak-Niedźwiedzka

Abstract: A thorough petrographic evaluation of aggregates from igneous rocks in terms of their alkali–silica reaction (ASR) potential is crucial in ensuring the durability and long-term performance of concrete structures, especially those where access to additional alkalis is possible, such as from de-icing agents. The aim of the research was to assess the potential reactivity of aggregates from igneous rocks, as only such aggregates are used for concrete airport pavements in Poland. Petrographic analysis was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Igneous rocks, also known as magmatic rocks, are one of the three main types of rocks that make up the Earth's lithosphere. According to statistics, igneous rocks account for 66% of the entire crust volume and are widely distributed (Antolik et al, 2023). Relevant studies (Piasta et al, 2016;Qaidi et al, 2022;Dobiszewska et al, 2023) have shown that some igneous rocks have certain pozzolanic activity after being processed to a certain fineness, and their active components SiO 2 and Al 2 O 3 can hydrate with cement clinker to produce calcium hydroxide and high-alkaline hydrated calcium silicate, and high-quality low-alkaline hydrated calcium silicate and hydrated calcium aluminate.…”
Section: Introductionmentioning
confidence: 99%
“…Igneous rocks, also known as magmatic rocks, are one of the three main types of rocks that make up the Earth's lithosphere. According to statistics, igneous rocks account for 66% of the entire crust volume and are widely distributed (Antolik et al, 2023). Relevant studies (Piasta et al, 2016;Qaidi et al, 2022;Dobiszewska et al, 2023) have shown that some igneous rocks have certain pozzolanic activity after being processed to a certain fineness, and their active components SiO 2 and Al 2 O 3 can hydrate with cement clinker to produce calcium hydroxide and high-alkaline hydrated calcium silicate, and high-quality low-alkaline hydrated calcium silicate and hydrated calcium aluminate.…”
Section: Introductionmentioning
confidence: 99%